Pengaruh Koneksi Politik dan Kepemilikan Asing terhadap Nilai Perusahaan - Rizky Maulana; Andreas Vernando (Universitas Pamulang, 2022)
This study investigates effect of political connections and foreign ownership on firm value. This study use 942 samples of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2018. The panel data regression method with the fixed effect model is employed in the analysis. The regression is processed with Stata 15. This study uses two dependent variables for estimating the firm value, Tobin’s Q and PBV. Furthermore, political connections and foreign ownership are main independent variables, and control variables are size, leverage, and growth. This study finds that political connections and foreign ownership have no effect on firm value.